PENGENDALIAN KUALITAS SEWING DI PT. BINA BUSANA INTERNUSA III SEMARANG - Endro Prihastono; Hayat Amirudin (Jurnal Ilmiah Dinamika Teknik, 2017)
In an effort to produce products that comply with the wishes of consumers, and that the company's products can compete in the market, the company is required to be able to produce high quality products. Thus, companies need to pay attention to quality control more carefully so that the product has a quality that correspond to consumer expectations. The background of the necessary implementation of quality control, for any problems faced by the company relating to quality control and Analyzing anything cause damage to the product. From the analysis of the general factors known to cause damage in the production of which is derived from human factors or labor, materials or raw materials, work methods, environmental and production machinery. Keywords: Quality,Causation